Cuentas por cobrar de catastro del Gobierno Autónomo Descentralizado Municipal del cantón Caluma, provincia de Bolívar, periodo 2022-2023. - Montes Veliz, Jonathan Cristian (2024)
The case study examines the state of accounts receivable for cadastral purposes of the GAD of Caluma during the periods 2022-2023, revealing significant issues in tax collection. Justified by the need to ensure the municipality's financial sustainability, the study focuses on identifying deficiencies in collection that limit the available income for essential community projects and services. The primary objective was to evaluate the accounts receivable by reviewing the institution's financial statements and accounting reports. Using a mixed methodology, a documentary review and a comparative analysis of the income budget schedules were conducted, allowing for horizontal analysis to measure the influence of accounts receivable. The results indicated a general decrease in income collection and an increase in accounts receivable, highlighting the need to improve the efficiency of urban property tax collection. In conclusion, the inefficiency in collection affects the GAD of Caluma's ability to finance projects and services, underscoring the importance of implementing effective strategies and strengthening fiscal control and monitoring mechanisms.